Heat shielding resin sheet material

The heat shielding resin sheet material, utilizing near-infrared absorbing composite tungsten oxide particles, addresses the challenge of balancing visible light transmittance and near-infrared shielding while ensuring weather resistance and physical integrity.

JP7673403B2Active Publication Date: 2025-05-09SUMITOMO METAL MINING CO LTD
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
JP2020215131
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-12-24
Publication Date
2025-05-09
Estimated Expiration
2040-12-24

AI Technical Summary

Technical Problem

Existing heat shielding materials for windows struggle to balance visible light transmittance and near-infrared shielding performance, while also maintaining weather resistance and physical properties like impact resistance.

Method used

A heat shielding resin sheet material incorporating particles of near-infrared absorbing composite tungsten oxide, specifically represented by the formula M_xW_yO_z, where M is an element such as tungsten, oxygen, and other metals, with a controlled ratio of x/y and z/y to achieve both effective near-infrared absorption and weather resistance.

Benefits of technology

The material achieves excellent weather resistance and maintains high visible light transmittance while efficiently shielding near-infrared rays, thereby effectively regulating room temperature without compromising physical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007673403000002
    Figure 0007673403000002
  • Figure 0007673403000003
    Figure 0007673403000003
  • Figure 0007673403000004
    Figure 0007673403000004
Patent Text Reader

Abstract

To provide a heat ray-shielding resin sheet material which is excellent in weather resistance.SOLUTION: A heat ray-shielding resin sheet material contains near infrared absorption material particles, and a resin, in which the near infrared absorption material particles contain particles of a composite tungsten oxide represented by general formula MxWyOz, in the general formula, an element M is one or more elements selected from H, He, an alkali metal, an alkali earth metal, a rare earth element, Mg, Zr, Cr, Mn, Fe, Ru, Co, Rh, Ir, Ni, Pd, Pt, Cu, Ag, Au, Zn, Cd, Al, Ga, In, Tl, Si, Ge, Sn, Pb, Sb, B, F, P, S, Se, Br, Te, Ti, Nb, V, Mo, Ta, Re, Be, Hf, Os, Bi and I, W is tungsten, O is oxygen, and 0.001≤x / y≤1 and 3.0<z / y.SELECTED DRAWING: Figure 3
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] The present invention relates to a heat ray shielding resin sheet material. [Background technology]

[0002] Conventionally, transparent glass or resin plates have been placed in so-called openings, such as windows in various buildings and vehicles, to let in sunlight. However, sunlight contains ultraviolet and infrared rays in addition to visible light, and among the infrared rays, near-infrared rays in the range of 800 to 2500 nm, known as heat rays, enter a room through an opening and cause the temperature inside the room to rise.

[0003] Therefore, in recent years, heat-shielding materials that can block heat rays while allowing sufficient visible light to enter as window materials for various buildings and vehicles, thereby maintaining brightness while simultaneously suppressing the rise in temperature inside the room, have been studied, and various means for achieving this have been proposed.

[0004] Patent Documents 1 and 2 propose heat ray reflective plates made by blending titanium oxide-coated mica with transparent resins such as methacrylic resins and polycarbonate resins. These heat ray reflective plates require the addition of a large amount of titanium oxide-coated mica (hereinafter referred to as "heat ray reflective particles") to enhance heat ray shielding performance. However, increasing the amount of heat ray reflective particles added results in a decrease in visible light transmittance. Conversely, decreasing the amount of heat ray reflective particles added increases visible light transmittance but decreases heat ray shielding performance, making it difficult to simultaneously satisfy both heat ray shielding and visible light transmittance. Furthermore, blending a large amount of heat ray reflective particles also has the drawback of reducing the physical properties of the transparent resin substrate, particularly impact resistance and toughness, resulting in a strength disadvantage.

[0005] The present applicant has proposed in Patent Document 3 an infrared-shielding material microparticle dispersion in which infrared material microparticles are dispersed in a medium, the infrared material microparticles containing tungsten oxide microparticles and / or composite tungsten oxide microparticles, and the dispersed particle diameter of the infrared material microparticles being 1 nm or more and 800 nm or less. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] Japanese Patent Application Publication No. 5-78544 [Patent Document 2] Japanese Patent Application Publication No. 2-173060 [Patent Document 3] International Publication No. 2005 / 037932 Summary of the Invention [Problem to be solved by the invention]

[0007] Patent Document 3 provides near-infrared shielding material microparticles, a near-infrared shielding material microparticle dispersion, a near-infrared shielding body, near-infrared shielding material microparticles, and a method for producing the same, which sufficiently transmit visible light, efficiently shield invisible near-infrared rays having wavelengths of 780 nm or more, and are transparent and do not change color. However, in recent years, performance such as weather resistance has also been required.

[0008] An object of one aspect of the present invention is to provide a heat ray shielding resin sheet material that is excellent in weather resistance. [Means for solving the problem]

[0009] In one aspect of the present invention, a near-infrared absorbing material particle and a resin are contained, The near-infrared absorbing material particles are represented by the general formula M x W y O z (However, the M element is Na, K, Rb, Cs, Ba, In, TlOne or more elements selected from the above, W is tungsten, O is oxygen, 0.20≦x / y≦0.37, 3.0 <z / y <3.4 The present invention provides a heat ray shielding resin sheet material containing particles of composite tungsten oxide represented by the formula: [Effects of the Invention]

[0010] According to one aspect of the present invention, a heat ray shielding resin sheet material having excellent weather resistance can be provided. [Brief explanation of the drawings]

[0011] [Figure 1] FIG. 1 is an explanatory diagram of a hybrid plasma reactor used in Example 1. [Figure 2] FIG. 1 is an explanatory diagram of a high-frequency plasma reactor used in Example 2. [Figure 3] Cross-sectional view of a heat-shielding resin sheet material with a hollow three-layer structure. [Figure 4] Cross-sectional view of a seven-layer hollow heat-shielding resin sheet material. DETAILED DESCRIPTION OF THE INVENTION

[0012] Hereinafter, near-infrared absorbing material particles that can be suitably used in the heat-ray shielding resin sheet material according to this embodiment and a method for producing the same will be described first in "1. Near-infrared absorbing material particles" and "2. Method for producing near-infrared absorbing material particles." Then, in "3. Heat-ray shielding resin sheet material" and "4. Method for producing heat-ray shielding resin sheet material," the heat-ray shielding resin sheet material according to this embodiment and a method for producing the same will be described in detail. 1. Near-infrared absorbing material particles The near-infrared absorbing material particles are represented by the general formula M x W y O z The tungsten oxide may contain particles of a composite tungsten oxide represented by the formula:

[0013] In the general formula above, the M element is one or more elements selected from H, He, alkali metals, alkaline earth metals, rare earth elements, Mg, Zr, Cr, Mn, Fe, Ru, Co, Rh, Ir, Ni, Pd, Pt, Cu, Ag, Au, Zn, Cd, Al, Ga, In, Tl, Si, Ge, Sn, Pb, Sb, B, F, P, S, Se, Br, Te, Ti, Nb, V, Mo, Ta, Re, Be, Hf, Os, Bi, and I. W is tungsten and O is oxygen. x, y, and z can satisfy 0.001 ≦ x / y ≦ 1 and 3.0 < z / y.

[0014] In order to obtain near-infrared absorbing material particles with excellent weather resistance, the inventors of the present invention have conducted intensive research. In this specification, excellent weather resistance means that the near-infrared absorption characteristics do not change significantly even when placed in a high-temperature environment.

[0015] Generally, it is known that a material containing free electrons exhibits a reflection absorption response due to plasma vibration with respect to electromagnetic waves having wavelengths from 200 nm to 2600 nm around the region of sunlight. And when the powder of the material containing the free electrons is made into particles smaller than the wavelength of light, it is known that geometric scattering in the visible light region (wavelength 380 nm or more and 780 nm or less) is reduced and transparency in the visible light region is obtained. In this specification, "transparency" is used to mean that there is little scattering and high transmittance with respect to light in the visible light region.

[0016] Tungsten oxide represented by the general formula WO 3-a and so-called tungsten bronzes obtained by adding a positive element such as Na to tungsten trioxide are known to be conductive materials and materials containing free electrons. And these materials have been suggested to have a response of free electrons to light in the near-infrared region through analysis of single crystals and the like.

[0017] Generally, since there are no effective free electrons in tungsten trioxide (WO3), it has few absorption and reflection characteristics in the near-infrared region and is not effective as a near-infrared absorption material. Here, it is known that by reducing the ratio of oxygen to tungsten in tungsten trioxide to less than 3, free electrons are generated in the tungsten oxide.

[0018] In addition, conventionally, an M element has been added to the tungsten oxide to form a composite tungsten oxide. With this configuration, free electrons are generated in the composite tungsten oxide, absorption characteristics derived from the free electrons are exhibited in the near-infrared region, and it is effective as a near-infrared absorption material around a wavelength of 1000 nm.

[0019] The inventors of the present invention conducted further research on tungsten oxides and composite tungsten oxides in order to obtain near-infrared absorption material particles with excellent weather resistance. As a result, in near-infrared absorption material particles containing particles of a composite tungsten oxide represented by the general formula M x W y O z it was found that by setting 3.0 < z / y with respect to y and z in the above general formula, both near-infrared absorption characteristics and weather resistance can be achieved, and the present invention was completed.

[0020] The near-infrared absorption material particles of the present embodiment can contain particles of a composite tungsten oxide represented by the general formula M as described above. The near-infrared absorption material particles of the present embodiment can also be composed of particles of a composite tungsten oxide represented by the above general formula. However, even in this case, it does not exclude containing inevitable components mixed in during the manufacturing process or the like.

[0021] ​​​​​​Here, as described above, from the viewpoint of enhancing stability, the M element in the above general formula is preferably one or more elements selected from H, He, alkali metals, alkaline earth metals, rare earth elements, Mg, Zr, Cr, Mn, Fe, Ru, Co, Rh, Ir, Ni, Pd, Pt, Cu, Ag, Au, Zn, Cd, Al, Ga, In, Tl, Si, Ge, Sn, Pb, Sb, B, F, P, S, Se, Br, Te, Ti, Nb, V, Mo, Ta, Re, Be, Hf, Os, Bi, and I. In particular, from the viewpoint of particularly improving the optical properties and weather resistance as a near-infrared absorbing material, the M element is more preferably an alkali metal, alkaline earth metal element, transition metal element, Group 4B element, or Group 5B element.

[0022] When composite tungsten oxide particles contain crystals having a hexagonal crystal structure, the particles have particularly improved transmittance in the visible light region and particularly improved absorption in the near-infrared region. The hexagonal crystal structure is formed by a group of six octahedra formed by WO6 units, which form hexagonal voids (tunnels), and each void is filled with an M element to form a single unit, and these single units are then aggregated together.

[0023] It should be noted that the composite tungsten oxide particles are not limited to those containing crystals having a hexagonal crystal structure, and for example, if they have a structure in which six octahedra formed from the above-mentioned unit structure, i.e., WO6 units, are assembled to form hexagonal voids, and the M element is arranged in the voids, it is possible to particularly improve the transmittance in the visible light region and particularly improve the absorption in the near-infrared region. Therefore, even if the composite tungsten oxide particles do not contain crystals having a hexagonal crystal structure and only have the above-mentioned unit structure, they can still achieve a high effect.

[0024] As described above, when composite tungsten oxide particles have a structure in which cations of the M element are added to hexagonal voids, absorption in the near-infrared region is particularly improved. Generally, adding an M element with a large ionic radius tends to form a hexagonal crystal or the above structure. Specifically, when the composite tungsten oxide contains one or more elements selected from Cs, Rb, K, Tl, In, Ba, Li, Ca, Sr, Fe, and Sn as the M element, the hexagonal crystal or the above structure is likely to form. Therefore, the composite tungsten oxide particles preferably contain one or more elements selected from Cs, Rb, K, Tl, In, Ba, Li, Ca, Sr, Fe, and Sn as the M element, and more preferably, the M element is one or more elements selected from Cs, Rb, K, Tl, In, Ba, Li, Ca, Sr, Fe, and Sn.

[0025] Furthermore, among these M elements having a large ionic radius, particles of a composite tungsten oxide containing one or more elements selected from Cs and Rb are likely to form hexagonal crystals or the above-mentioned structure, and can achieve both absorption in the near-infrared region and transmission in the visible light region, while also exhibiting particularly high performance.

[0026] When particles of a composite tungsten oxide having a hexagonal crystal structure have a uniform crystal structure, x / y, which indicates the content ratio of element M relative to 1 mole of tungsten, is preferably 0.2 or more and 0.5 or less, and more preferably 0.33. When the value of x / y is 0.33, it is believed that element M is arranged in all of the hexagonal voids.

[0027] The composite tungsten oxide particles are also effective as a near-infrared absorbing material when they contain crystals other than the above-mentioned hexagonal crystals, such as tetragonal crystals or cubic crystals.

[0028] The cubic and tetragonal composite tungsten oxides each have a suitable range and upper limit of the amount of element M added, which is derived from their structures, and the upper limit of x / y, which is the content ratio of M element to 1 mole of tungsten, is 1 mole in the case of a cubic crystal, and about 0.5 moles in the case of a tetragonal crystal. Note that the upper limit of x / y, which is the content ratio of M element to 1 mole of tungsten, varies depending on the type of M element, etc., but in the case of a tetragonal crystal, about 0.5 moles is easy to industrially produce.

[0029] However, it is difficult to simply define these structures, and the ranges are examples showing particularly basic ranges, so the present invention is not limited to these.

[0030] Depending on the crystal structure contained in the composite tungsten oxide particles, the absorption position in the near-infrared region tends to change. The absorption position in the near-infrared region tends to shift toward longer wavelengths in tetragonal crystals compared to cubic crystals, and furthermore, the absorption position in the hexagonal crystals tends to shift toward longer wavelengths compared to tetragonal crystals. Furthermore, accompanying this shift in absorption position, absorption in the visible light region is lowest in hexagonal crystals, followed by tetragonal crystals, with cubic crystals having the highest absorption. Therefore, it is preferable to select the crystal system contained depending on the required performance, etc. For example, when used in applications requiring greater transmission of light in the visible light region and greater absorption of light in the near-infrared region, it is preferable that the composite tungsten oxide particles contain hexagonal crystals. However, the trends in the optical properties described here are merely rough trends, and will vary depending on the type and amount of added element and the amount of oxygen, and the present invention is not limited thereto.

[0031] By combining the above-mentioned control of the oxygen content with the addition of an element M that generates free electrons to the composite tungsten oxide, a near-infrared absorbing material with better weather resistance can be obtained. The general formula of the composite tungsten oxide, which is a near-infrared absorbing material that combines the control of the oxygen content and the addition of an element M that generates free electrons, is x W y O zWhen described as such, x and y can satisfy 0.001 ≦ x / y ≦ 1, and preferably satisfy 0.20 ≦ x / y ≦ 0.37.

[0032] Also, for y and z in the above general formula, the relationship 3.0 < z / y is satisfied, preferably 3.0 < z / y < 3.4 is satisfied, more preferably 3.0 < z / y < 3.3 is satisfied, and even more preferably 3.0 < z / y < 3.22 is satisfied.

[0033] According to the study of the present applicant, for composite tungsten oxide particles having a hexagonal crystal structure, when z / y = 3, it is considered that the element M is arranged in all the hexagonal voids when the value of x / y becomes 0.33.

[0034] It has been confirmed by chemical analysis that the composite tungsten oxide particles contained in the near-infrared absorbing material particles according to the present embodiment have z / y exceeding 3. On the other hand, it has been confirmed by powder X-ray diffraction that the composite tungsten oxide particles contained in the near-infrared absorbing material particles according to the present embodiment may take a tungsten bronze structure of at least one of tetragonal, cubic, and hexagonal when z / y = 3. Therefore, it is preferable that the particles of the composite tungsten oxide contained in the near-infrared absorbing material particles according to the present embodiment contain crystals having one or more crystal structures selected from hexagonal, tetragonal, and cubic crystals. By containing crystals of the above crystal structure, particularly excellent near-infrared absorption characteristics and visible light transmittance characteristics can be exhibited.

[0035] By the way, it is considered that oxygen atoms when the z / y value exceeds 3 penetrate into the crystals of the composite tungsten oxide particles. As a result, by oxygen atoms penetrating into the crystals, it is considered that excellent weather resistance can be realized without the crystals of the composite tungsten oxide particles deteriorating even when exposed to heat or moisture.

[0036] The crystal structure of the particles of the composite tungsten oxide contained in the near-infrared absorbing material particles according to the present embodiment can be confirmed by an X-ray diffraction pattern by the powder X-ray diffraction method (θ-2θ method).

[0037] The near-infrared absorbing material particles of this embodiment exhibit light transmission characteristics having a maximum value in a wavelength range of 350 nm or more and 600 nm or less and a minimum value in a wavelength range of 800 nm or more and 2100 nm or less, and can exhibit excellent near-infrared absorbing effect and weather resistance. The near-infrared absorbing material particles of this embodiment more preferably have a maximum value in a wavelength range of 440 nm or more and 600 nm or less and a minimum value in a wavelength range of 1150 nm or more and 2100 nm or less.

[0038] Furthermore, the near-infrared absorbing material particles according to this embodiment preferably have a particle diameter of 100 nm or less. From the viewpoint of exhibiting better near-infrared absorbing properties, the particle diameter is more preferably 10 nm or more and 100 nm or less, even more preferably 10 nm or more and 80 nm or less, particularly preferably 10 nm or more and 60 nm or less, and most preferably 10 nm or more and 40 nm or less. When the particle diameter of the near-infrared absorbing material particles is in the range of 10 nm or more and 40 nm or less, the best near-infrared absorbing properties are exhibited.

[0039] Here, the particle size refers to the size of each individual near-infrared absorbing material particle that is not aggregated, that is, the particle size of each individual particle.

[0040] The particle size here does not include the size of aggregates of near-infrared absorbing material particles, and is different from the dispersed particle size.

[0041] The particle diameter here can be calculated by, for example, measuring the particle diameters of multiple particles using a transmission electron microscope (TEM) or the like while the near-infrared absorbing material particles are dispersed. Note that since near-infrared absorbing material particles are usually irregular in shape, the diameter of the smallest circle circumscribing the particle can be used as the particle diameter of the particle. For example, when the particle diameters of multiple particles are measured particle by particle using a transmission electron microscope as described above, it is preferable that the particle diameters of all particles satisfy the above range. The number of particles to be measured is not particularly limited, but is preferably, for example, 10 to 50.

[0042] Furthermore, from the viewpoint of exhibiting excellent near-infrared absorption properties, the crystallite diameter of the composite tungsten oxide particles is preferably 10 nm or more and 100 nm or less, more preferably 10 nm or more and 80 nm or less, even more preferably 10 nm or more and 60 nm or less, and particularly preferably 10 nm or more and 40 nm or less. This is because, if the crystallite diameter is in the range of 10 nm or more and 40 nm or less, particularly excellent near-infrared absorption properties are exhibited. The crystallite diameter of the composite tungsten oxide particles contained in the near-infrared absorbing material particles can be calculated using the Rietveld method from the X-ray diffraction pattern measured by powder X-ray diffraction (θ-2θ method).

[0043] Furthermore, near-infrared absorbing material particle dispersions containing particles of the composite tungsten oxide according to this embodiment largely absorb light in the near-infrared region, particularly light with a wavelength around 1000 nm, and therefore the transmitted color tone is often blue to green.

[0044] The dispersed particle diameter of the near-infrared absorbing material particles of this embodiment can be selected depending on the intended use. First, when used in an application that requires maintaining transparency, it is preferable that the dispersed particle diameter is 800 nm or less. This is because particles with a dispersed particle diameter of 800 nm or less do not completely block light due to scattering, and can maintain visibility in the visible light region while efficiently maintaining transparency.

[0045] In particular, when transparency in the visible light region is important, it is preferable to further consider scattering by particles. Note that the dispersed particle size includes the size of an aggregate of near-infrared absorbing material particles, and is different from the particle size described above.

[0046] When prioritizing the reduction of scattering by the particles, the dispersed particle diameter of the near-infrared absorbing material particles of this embodiment is preferably 200 nm or less, more preferably 10 nm to 200 nm, and even more preferably 10 nm to 100 nm. This is because a small dispersed particle diameter reduces scattering of light in the visible light region with wavelengths of 380 nm to 780 nm due to geometric scattering or Mie scattering, thereby preventing a dispersion containing the near-infrared absorbing material particles of this embodiment from becoming like frosted glass and losing clear transparency. That is, when the dispersed particle diameter is 200 nm or less, the geometric scattering or Mie scattering is reduced, resulting in a Rayleigh scattering region. In the Rayleigh scattering region, scattered light is proportional to the sixth power of the dispersed particle diameter, so scattering is reduced as the dispersed particle diameter decreases, improving transparency. Furthermore, a dispersed particle diameter of 100 nm or less is preferable because scattered light is significantly reduced. From the perspective of avoiding light scattering, a small dispersed particle diameter is preferable, and a dispersed particle diameter of 10 nm or more facilitates industrial production.

[0047] By setting the dispersed particle diameter to 800 nm or less, the haze (haze value) of the near-infrared absorbing material particle dispersion in which near-infrared absorbing material particles are dispersed in a medium can be set to 10% or less at a visible light transmittance of 85% or less. In particular, by setting the dispersed particle diameter to 100 nm or less, the haze can be set to 1% or less.

[0048] The light scattering of the near-infrared absorbing material particle dispersion must be considered in terms of the dispersion particle diameter, since it is necessary to take into account the aggregation of the near-infrared absorbing material particles. 2. Method for producing near-infrared absorbing material particles A configuration example of a method for producing near-infrared absorbing particles will be described. According to the method for producing near-infrared absorbing particles of this embodiment, the near-infrared absorbing particles described above can be produced. Therefore, some of the matters already described will not be described again.

[0049] The near-infrared absorbing material particles of this embodiment contain the above-described general formula M x W y O zThe composite tungsten oxide particles represented by the formula (I) can be produced by, for example, the following solid-state reaction method or plasma method.

[0050] Each method will be explained below. (1) Solid-state reaction method When composite tungsten oxide particles are produced by a solid-state reaction method, the following steps may be included.

[0051] A tungsten compound and an M element compound are mixed to prepare a raw material mixture (mixing step). Preferably, the raw material mixture is blended and mixed so that the molar ratio of the M element to tungsten in the raw material mixture is the ratio of x to y in the above general formula of the target composite tungsten oxide particles.

[0052] The raw material mixture obtained in the mixing step is heat-treated in an atmosphere containing oxygen (first heat-treatment step).

[0053] The heat-treated product obtained after the first heat treatment step is heat-treated in a reducing gas atmosphere, a mixed gas atmosphere of a reducing gas and an inert gas, or an inert gas atmosphere (second heat treatment step).

[0054] After the second heat treatment step, if necessary, a pulverization treatment or the like may be carried out so that the particles of the near-infrared absorbing material have a desired particle size.

[0055] The near-infrared absorbing material particles of the present embodiment, including the composite tungsten oxide particles obtained by the above steps, have sufficient near-infrared absorbing power and have properties preferred as near-infrared absorbing material particles. In addition, the near-infrared absorbing material particles can be excellent in weather resistance.

[0056] Each step will be described in detail below. (Mixing process) The tungsten compound to be subjected to the mixing step can be one or more compounds selected from the group consisting of tungsten acid (H2WO4), ammonium tungstate, tungsten hexachloride, and tungsten hydrate obtained by adding water to tungsten hexachloride dissolved in alcohol to hydrolyze it, and then evaporating the solvent.

[0057] The M element compound to be subjected to the mixing step may be, for example, one or more selected from oxides, hydroxides, nitrates, sulfates, chlorides, and carbonates of the M element.

[0058] In the mixing step, when mixing the tungsten compound and the M element compound, the mass ratio (M:W) of the M element (M) to tungsten (W) in the resulting raw material mixture is adjusted to satisfy the target general formula M x W y O z It is preferable to mix the raw materials so that x:y is equal to the above.

[0059] The mixing method is not particularly limited, and either wet mixing or dry mixing can be used. In the case of wet mixing, a mixed powder of the M element compound and the tungsten compound is obtained by drying the mixture obtained after wet mixing. The drying temperature and time after wet mixing are not particularly limited.

[0060] The dry mixing may be carried out using a known mixing device such as a commercially available crusher, kneader, ball mill, sand mill, or paint shaker, and there are no particular limitations on the mixing conditions such as the mixing time and mixing speed. (First heat treatment step) The heat treatment temperature in the first heat treatment step is not particularly limited, but is preferably higher than the temperature at which the composite tungsten oxide particles crystallize, specifically, for example, 500°C or higher and 1000°C or lower, and more preferably 500°C or higher and 800°C or lower. (Second heat treatment process) In the second heat treatment step, as described above, heat treatment can be performed in a reducing gas atmosphere, a mixed gas atmosphere of a reducing gas and an inert gas, or an inert gas atmosphere at a temperature of 500°C or higher and 1200°C or lower.

[0061] When a reducing gas is used in the second heat treatment step, the type of reducing gas is not particularly limited, but hydrogen (H2) is preferred. Furthermore, when hydrogen is used as the reducing gas, its concentration is not particularly limited and can be appropriately selected depending on the firing temperature, the amount of the starting materials, etc. For example, it is 20 vol% or less, preferably 10 vol% or less, and more preferably 7 vol% or less. A reducing gas concentration of 20 vol% or less can avoid the formation of WO2, which does not have solar radiation shielding properties, due to rapid reduction. (2) Plasma method The near-infrared absorbing material particles of this embodiment contain the above-described general formula M x W y O z The composite tungsten oxide particles represented by the formula (I) can also be produced by, for example, a plasma method. When producing near-infrared absorbing material particles by a plasma method, the following steps can be included.

[0062] As a starting material, a raw material mixture of a tungsten compound and an M element compound, or a compound represented by the general formula M x W y O z´ A composite tungsten oxide precursor represented by the following formula is prepared (raw material preparation step).

[0063] The starting material prepared in the raw material preparation step is supplied to plasma together with a carrier gas, and undergoes evaporation and condensation processes to produce the desired composite tungsten oxide particles (reaction step). (Raw material preparation process) When preparing a raw material mixture of a tungsten compound and an M element compound as a starting material, it is preferable to blend and mix the raw materials so that the mass ratio (M:W) of the M element (M) to tungsten (W) in the raw material mixture of the tungsten compound and the M element compound is equal to the ratio x:y of x to y in the general formula of the target composite tungsten oxide described above.

[0064] As for the tungsten compound and the M element compound, the same materials as those described in the solid-phase reaction method can be preferably used, and thus the description thereof is omitted here.

[0065] Also, in the composite tungsten oxide precursor represented by the general formula M x W y O z´ M can be the aforementioned M element, W can be tungsten, and O can be oxygen. It is preferable that x, y, and z´ satisfy 0.001 ≦ x / y ≦ 1 and 2.0 < z´ / y.

[0066] In the general formula M x W y O z´ The composite tungsten oxide precursor represented by can be synthesized by, for example, the aforementioned solid-phase reaction method. The x / y in such a composite tungsten oxide precursor is preferably a material that matches the x / y in the particles of the composite tungsten oxide represented by the target general formula M x W y O z (Reaction step) As the carrier gas for transporting the starting materials in the reaction step, a mixed gas of an inert gas and an oxygen gas can be used.

[0067] The plasma can be generated, for example, in an atmosphere of an inert gas alone or a mixed gas of an inert gas and a hydrogen gas. The plasma is not particularly limited, but a thermal plasma is preferable. The raw materials supplied into the plasma evaporate instantaneously, and the evaporated raw materials condense in the process of reaching the plasma tail flame part and are rapidly solidified outside the plasma flame to generate particles of the composite tungsten oxide. According to the plasma method, for example, particles of a composite tungsten oxide with a single crystal phase can be generated.

[0068] ​The plasma used in the method for producing near-infrared absorbing material particles of this embodiment is preferably, for example, any one of DC arc plasma, high-frequency plasma, microwave plasma, and low-frequency AC plasma, or a combination of these, or plasma obtained by an electrical method in which a magnetic field is applied to DC plasma, plasma obtained by a high-power laser, or plasma obtained by a high-power electron beam or ion beam. Whichever thermal plasma is used, it is preferably a thermal plasma having a high-temperature portion of 10,000 K or higher, more preferably 10,000 K or higher and 25,000 K or lower, and in particular, plasma in which the particle generation time can be controlled.

[0069] A specific example of the configuration of the reaction step in the method for producing near-infrared absorbing material particles of this embodiment by a plasma method will be described with reference to FIG.

[0070] The device shown in FIG. 1 is a hybrid plasma reactor 10 in which a DC plasma device and a high frequency plasma device are superimposed.

[0071] The hybrid plasma reactor 10 has a water-cooled quartz double tube 11 and a reaction vessel 12 connected to the water-cooled quartz double tube 11. A vacuum exhaust device 13 is connected to the reaction vessel 12.

[0072] A DC plasma torch 14 is provided above the water-cooled quartz double tube 11, and the DC plasma torch 14 is provided with a plasma generation gas supply port 15.

[0073] The system is configured so that sheath gas for generating high-frequency plasma and protecting the quartz tube can be supplied along the inner wall of the water-cooled quartz double tube 11 outside the plasma region, and a sheath gas inlet 16 is provided on the upper flange of the water-cooled quartz double tube 11.

[0074] A water-cooled copper coil 17 for generating high-frequency plasma is arranged around the water-cooled quartz double tube 11 .

[0075] A raw material powder carrier gas supply port 18 is provided near the DC plasma torch 14 and is connected by piping to a raw material powder supply device 19 that supplies raw material powder.

[0076] A gas supply device 20 can be connected by piping to the plasma generation gas supply port 15, the sheath gas inlet 16, and the raw material powder supply device 19, so that a predetermined gas can be supplied to each component from the gas supply device 20. If necessary, supply ports can be provided in addition to the components described above so that the components in the device can be cooled or a predetermined atmosphere can be created, and these can be connected to the gas supply device 20.

[0077] An example of the configuration of a method for producing composite tungsten oxide particles using the hybrid plasma reactor 10 will be described.

[0078] First, the reaction system consisting of the water-cooled quartz double tube 11 and the reaction vessel 12 is evacuated using the vacuum exhaust device 13. The degree of vacuum at this time is not particularly limited, but it can be evacuated to, for example, about 0.1 Pa (about 0.001 Torr). After the reaction system is evacuated, argon gas is supplied from the gas supply device 20, and the reaction system can be filled with argon gas. For example, it is preferable to have an argon gas flow system at 1 atmosphere within the reaction system.

[0079] Thereafter, a plasma gas can be supplied into the reaction vessel 12. The plasma gas is not particularly limited, but can be any gas selected from, for example, argon gas, a mixed gas of argon and helium (Ar-He mixed gas), a mixed gas of argon and nitrogen (Ar-N mixed gas), neon, helium, and xenon.

[0080] The supply flow rate of the plasma gas is not particularly limited, but for example, it can be introduced from the plasma generating gas supply port 15 at a flow rate of preferably 3 L / min to 30 L / min, more preferably 3 L / min to 15 L / min. Then, DC plasma can be generated.

[0081] Meanwhile, outside the plasma region, sheath gas for generating high-frequency plasma and protecting the quartz tube can be supplied in a spiral pattern from sheath gas inlet 16 along the inner wall of water-cooled quartz double tube 11. There are no particular limitations on the type or supply rate of the sheath gas, but for example, argon gas at 20 L / min to 50 L / min and hydrogen gas at 1 L / min to 5 L / min can be flowed to generate high-frequency plasma.

[0082] A high frequency power supply can then be applied to the water-cooled copper coil 17 for generating high frequency plasma. The conditions of the high frequency power supply are not particularly limited, but for example, a high frequency power supply of about 4 MHz and 15 kW to 50 kW can be applied.

[0083] After generating such a hybrid plasma, the raw material can be introduced using a carrier gas from a raw material powder carrier gas supply port 18 by a raw material powder supply device 19. There are no particular limitations on the carrier gas, and for example, a mixed gas consisting of argon gas at 1 L / min to 8 L / min and oxygen gas at 0.001 L / min to 0.8 L / min can be used.

[0084] The starting material mixture or composite tungsten oxide precursor is introduced into the plasma to carry out the reaction. The supply rate of the starting material from the raw material powder carrier gas supply port 18 is not particularly limited, but is preferably 1 g / min to 50 g / min, more preferably 1 g / min to 20 g / min.

[0085] By setting the feed rate of the starting material to 50 g / min or less, the proportion of the starting material passing through the center of the plasma flame can be sufficiently increased, the proportion of unreacted materials and intermediate products can be suppressed, and the proportion of the desired composite tungsten oxide particles produced can be increased. Also, by setting the feed rate of the starting material to 1 g / min or more, productivity can be increased.

[0086] The starting material supplied to the plasma is instantly vaporized in the plasma and undergoes a condensation process to produce composite tungsten oxide particles with an average primary particle size of 100 nm or less.

[0087] The particle size of the composite tungsten oxide particles obtained by the manufacturing method of this embodiment can be easily controlled by the plasma output, plasma flow rate, the amount of raw material powder supplied, and the like.

[0088] After the reaction, the composite tungsten oxide particles produced are deposited in the reaction vessel 12 and can be recovered.

[0089] The method for producing near-infrared absorbing particles of the present embodiment has been described above. The near-infrared absorbing particles obtained by this production method can be evaluated and confirmed, for example, by the following method.

[0090] For example, the constituent elements of the near-infrared absorbing material particles obtained by the above-mentioned method for producing near-infrared absorbing material particles can be quantitatively analyzed by chemical analysis. The analytical method is not particularly limited, but for example, the M element and tungsten can be analyzed by plasma emission spectroscopy, and oxygen can be analyzed by inert gas impulse heating fusion infrared absorption spectroscopy.

[0091] The crystal structure of the composite tungsten oxide particles contained in the near-infrared absorbing material particles can be confirmed by powder X-ray diffraction.

[0092] The particle size of the near-infrared absorbing material particles can be confirmed by particle size measurement based on TEM observation or dynamic light scattering. 3. Heat-shielding resin sheet material The heat ray shielding resin sheet material of this embodiment (hereinafter, may be referred to as "resin sheet material") can contain the near-infrared absorbing material particles described above and a resin.

[0093] The near-infrared absorbing material particles have already been explained, so the explanation will be omitted here.

[0094] The resin can be selected depending on the application of the heat ray-shielding resin sheet material, and for example, various transparent resins can be used. In particular, from the viewpoints of optical properties, mechanical properties, raw material costs, etc., the resin is preferably a polycarbonate resin or an acrylic resin.

[0095] When a polycarbonate resin is used as the resin for the heat-shielding resin sheet material, the polycarbonate resin can be obtained, for example, by reacting a dihydric phenol with a carbonate precursor by a solution method or a melting method. Representative examples of dihydric phenols include 2,2-bis(4-hydroxyphenyl)propane (bisphenol A), 1,1-bis(4-hydroxyphenyl)ethane, 1,1-bis(4-hydroxyphenyl)cyclohexane, 2,2-bis(4-hydroxy-3,5-dimethylphenyl)propane, 2,2-bis(4-hydroxy-3,5-dibromophenyl)propane, 2,2-bis(4-hydroxy-3-methylphenyl)propane, bis(4-hydroxyphenyl)sulfide, and bis(4-hydroxyphenyl)sulfone. Furthermore, the dihydric phenol is preferably a bis(4-hydroxyphenyl)alkane, and more preferably one containing bisphenol A as the main component.

[0096] The acrylic resin may be a polymer or copolymer that uses methyl methacrylate, ethyl methacrylate, propyl methacrylate, or butyl methacrylate as the main raw material, and, if necessary, an acrylic acid ester having an alkyl group having 1 to 8 carbon atoms, vinyl acetate, styrene, acrylonitrile, methacrylonitrile, or the like as a copolymerization component. Furthermore, an acrylic resin that has been polymerized in multiple stages may also be used.

[0097] In the resin sheet material of this embodiment, the near-infrared absorbing material particles can be blended into the resin, and are preferably dispersed in the resin, and more preferably uniformly dispersed in the resin.

[0098] In the resin sheet material of this embodiment, the resin can be molded into a desired shape, and the shape is not particularly limited, but can be, for example, a sheet shape. However, the thickness of the sheet is not particularly limited, and can be adjusted to any thickness as needed, for example, from a thick plate shape to a thin film shape. In addition, it is preferable that near-infrared absorbing material particles are dispersed in the resin having a sheet shape, as described above.

[0099] As described above, the resin sheet material of this embodiment can contain, for example, a resin blended with near-infrared absorbing material particles. However, the resin sheet material of this embodiment is not limited to this form, and can further include any optional components as needed. The resin sheet material of this embodiment can also include, for example, an ultraviolet absorbing film or a hard coat layer, which will be described below.

[0100] For example, the heat ray shielding resin sheet material may have an ultraviolet absorbing film, which is a resin coating containing an ultraviolet absorbing agent, on the surface of a sheet made of a resin containing at least near-infrared absorbing material particles.

[0101] By having an ultraviolet absorbing film in the heat ray shielding resin sheet material, it is possible to further improve the weather resistance of the heat ray shielding resin sheet material, and also to provide the heat ray shielding resin sheet material with an ultraviolet shielding effect.

[0102] Furthermore, the heat ray-shielding resin sheet material may have a hard coat layer having scratch resistance on the surface of the sheet made of a resin containing at least near-infrared absorbing material particles. By having the hard coat layer, it is possible to improve the scratch resistance of the heat ray-shielding resin sheet material, and the heat ray-shielding resin sheet material can be suitably applied to windows of vehicles and automobiles.

[0103] Furthermore, the heat ray-shielding resin sheet material of this embodiment can also be configured to have a plurality of sheet layers containing at least the resins described above, and one or more of the plurality of sheet layers containing near-infrared absorbing material particles.

[0104] Specifically, the heat-shielding resin sheet material can have sheet layers including a first surface sheet layer, a second surface sheet layer, an intermediate sheet layer, and a connecting sheet layer. The first surface sheet layer can include a first surface, which is the outer surface of the heat-shielding resin sheet material. The second surface sheet layer can include a second surface, which is the outer surface of the heat-shielding resin sheet material, located opposite the first surface. The intermediate sheet layer can be disposed between the first surface sheet layer and the second sheet layer. That is, the first surface sheet layer, the intermediate sheet layer, and the second surface sheet layer can be disposed and stacked in that order. The connecting sheet layer can connect the first surface sheet layer, the intermediate sheet layer, and the second surface sheet layer.

[0105] A gap may be formed between the first and second surface sheet layers, i.e., the heat ray shielding resin sheet material of this embodiment may have a hollow multi-layer structure including a gap.

[0106] The outer surface means the surface exposed to the outside of the heat ray shielding resin sheet material.

[0107] As examples of such heat ray-shielding resin sheet materials, a heat ray-shielding resin sheet material 50 having a hollow three-layer structure shown in Fig. 3 and a heat ray-shielding resin sheet material 60 having a hollow seven-layer structure shown in Fig. 4 will be described. Figs. 3 and 4 show schematic cross-sectional views of a plane parallel to the lamination direction of the first surface sheet layer, second surface sheet layer, and intermediate sheet layer included in the heat ray-shielding resin sheet material.

[0108] The heat-shielding resin sheet material 50 shown in Figure 3 has an intermediate sheet layer 53 between opposing first and second surface sheet layers 51 and 52, and is arranged approximately parallel to the first and second surface sheet layers 51 and 52.

[0109] The first surface sheet layer 51 and the second surface sheet layer 52 each include a first outer surface 501 and a second outer surface 502 which are the outer surfaces of the heat ray shielding resin sheet material 50 .

[0110] The heat-ray shielding resin sheet material 50 is formed by connecting and integrating the first surface sheet layer 51, the second surface sheet layer 52, and the intermediate sheet layer 53 with a connecting sheet layer 54 that is approximately perpendicular to the first surface sheet layer 51, the second surface sheet layer 52, and the intermediate sheet layer 53. The first surface sheet layer 51, the second surface sheet layer 52, and the intermediate sheet layer 53 form a three-layer structure, and a hollow portion 55 is formed surrounded by the first surface sheet layer 51, the second surface sheet layer 52, the intermediate sheet layer 53, and the connecting sheet layer 54.

[0111] The heat-shielding resin sheet material 60 shown in Fig. 4 has four intermediate sheet layers provided between opposing first and second surface sheet layers 61 and 62. The first surface sheet layer 61 and the second surface sheet layer 62 each include a first outer surface 601 and a second outer surface 602, which are the outer surfaces of the heat-shielding resin sheet material 60. The intermediate sheet layers include a first intermediate sheet layer 63, a second intermediate sheet layer 64, a third intermediate sheet layer 65, and a fourth intermediate sheet layer 66, and the intermediate sheet layers are arranged approximately parallel to each other and at approximately equal intervals.

[0112] A first connecting sheet layer 67, which is orthogonal to the first surface sheet layer 61, second surface sheet layer 62, and four intermediate sheet layers, connects and integrates the first surface sheet layer 61, second surface sheet layer 62, and first intermediate sheet layer 63 to fourth intermediate sheet layer 66. A second connecting sheet layer 68, which has a substantially sinusoidal waveform and meanders at the arrangement pitch of the first connecting sheet layer 67, contacts the first surface sheet layer 61 and the second surface sheet layer 62. The second connecting sheet layer 68 intersects with the first intermediate sheet layer 63 to fourth intermediate sheet layer 66, and connects and integrates the first surface sheet layer 61, second surface sheet layer 62, and first intermediate sheet layer 63 to fourth intermediate sheet layer 66.

[0113] The heat-ray shielding resin sheet material 60 has a seven-layer structure made up of a first surface sheet layer 61, a second surface sheet layer 62, a first intermediate sheet layer 63 to a fourth intermediate sheet layer 66, and a second connecting sheet layer 68. A hollow portion 69 is formed surrounded by the first surface sheet layer 61, the second surface sheet layer 62, the first intermediate sheet layer 63 to the fourth intermediate sheet layer 66, the first connecting sheet layer 67, and the second connecting sheet layer 68.

[0114] In the heat ray shielding resin sheet material having a hollow multilayer structure as described above, all of the sheet layers, i.e., the first surface sheet layer, the second surface sheet layer, the intermediate sheet layer, and the connecting sheet layer, may contain near-infrared absorbing material particles.

[0115] However, without being limited to the above-mentioned form, for example, near-infrared absorbing material particles may be contained in only some of the sheet layers of the heat-shielding resin sheet material. For example, in the heat-shielding resin sheet material, only one of the first surface sheet layer including the outer surface and the second surface sheet layer may contain near-infrared absorbing material particles. Also, in the heat-shielding resin sheet material, only two layers, the first surface sheet layer including the outer surface of the resin sheet material and the second surface sheet layer, may contain near-infrared absorbing material particles.

[0116] For example, in the heat ray shielding resin sheet material 50 shown in Fig. 3, near-infrared absorbing material particles may be contained in all of the sheet layers, i.e., the first surface sheet layer 51, the second surface sheet layer 52, the intermediate sheet layer 53, and the connecting sheet layer 54, using an existing multilayer hollow sheet manufacturing device. Alternatively, near-infrared absorbing material particles may be contained only in the first surface sheet layer 51, or only in the first surface sheet layer 51 and the second surface sheet layer 52.

[0117] 4, near-infrared absorbing material particles may be contained in all of the sheet layers, namely, the first surface sheet layer 61, the second surface sheet layer 62, the first intermediate sheet layer 63 to the fourth intermediate sheet layer 66, the first connecting sheet layer 67, and the second connecting sheet layer 68. Alternatively, near-infrared absorbing material particles may be contained only in the first surface sheet layer 61 or the second surface sheet layer 62, or only in the first surface sheet layer 61 and the second surface sheet layer 62.

[0118] By making the heat-shielding resin sheet material have the hollow multilayer structure as described above, it is possible to provide an air layer with heat insulating effect between the surface sheet layer and the intermediate sheet layer, which prevents the surface sheet layer on the outdoor side from absorbing solar energy and releases the solar energy to the outdoor side efficiently, thereby improving the heat-shielding effect.

[0119] Furthermore, by incorporating near-infrared absorbing material particles in only one or two surface sheet layers of the hollow multilayer structure, it becomes possible to incorporate more near-infrared absorbing material particles in the surface sheet layer on the outdoor side, for example. By adopting this configuration, it is possible to further improve, for example, the suppression of solar energy release to the indoor side, while maintaining the near-infrared absorbing material particles per unit area of ​​the heat-shielding resin sheet material constant.

[0120] When a plurality of sheet layers contain near-infrared absorbing material particles, the content ratio of the near-infrared absorbing material particles may differ for each sheet layer.

[0121] When some of the sheet layers do not contain near-infrared absorbing material particles, the type of resin constituting the sheet layer is not particularly limited, and for example, various transparent resins can be used. As the resin constituting the sheet layer not containing near-infrared absorbing material particles, a polycarbonate resin or an acrylic resin can be suitably used.

[0122] When the heat-shielding resin sheet material has multiple sheet layers as described above, the type of resin may be different for each sheet layer, but from the viewpoint of reducing manufacturing costs and improving productivity, it is preferable that the resin contained in the multiple sheet layers is the same.

[0123] When a heat-shielding resin sheet material has multiple sheet layers, there does not need to be a clear boundary between each sheet layer that makes up the heat-shielding resin sheet material, and the layers can be given names as described above for convenience depending on their arrangement.

[0124] Any of the heat ray-shielding resin sheet materials described above can be laminated on other resin sheet materials depending on the application to form a heat ray-shielding resin sheet material laminate. By using a heat ray-shielding resin sheet material as a heat ray-shielding resin sheet material laminate, a laminate exhibiting a variety of mechanical properties can be obtained, and by using a heat ray-shielding resin sheet material in all or part of the laminate, a laminate having desired optical properties can be obtained.

[0125] It is also preferable to construct an architectural structure using the heat-shielding resin sheet material and the heat-shielding resin sheet material laminate described above, either alone or in combination. For example, by fixing the heat-shielding resin sheet material to a metal frame made of aluminum or the like with bolts, it is possible to efficiently block solar energy over a wider range. Furthermore, by processing the heat-shielding resin sheet material into any shape and using it as a rear window, sunroof, etc. in an automobile, it is possible to efficiently suppress temperature increases inside the vehicle.

[0126] A heat-shielding resin sheet laminate obtained by laminating a heat-shielding resin sheet material and glass can be fitted into the window frames of vehicles or used on the roofs, walls, and ceiling domes of buildings. In this case, the heat-shielding resin sheet material is placed on the exterior side of the room. By using it in this manner, it is possible to block incoming solar energy to reduce the load on the air conditioner, while also providing functions such as preventing glass from being shattered by flying stones, etc.

[0127] The heat ray-shielding resin sheet material described above uses near-infrared absorbing material particles that have excellent weather resistance, so the heat ray-shielding resin sheet material also has excellent weather resistance, making it possible to stably shield heat rays over a long period of time. 4. Manufacturing method of heat-shielding resin sheet material The method for producing the heat ray-shielding resin sheet material of the present embodiment is not particularly limited. The method for producing the heat ray-shielding resin sheet material of the present embodiment can include, for example, a mixture preparation step of adding the above-described near-infrared absorbing material particles to at least a part of a resin and dispersing them as needed to prepare a mixture, and a molding step of molding the mixture into a desired shape.

[0128] In the mixing step, the method for adding and dispersing the near-infrared absorbing material particles in the resin is not particularly limited, and any method can be selected. For example, a method can be used in which the near-infrared absorbing material particles are directly added to the resin and melt-mixed. Another example is a method in which an additive liquid in which the near-infrared absorbing material particles are dispersed in an arbitrary dispersion medium is prepared in advance, and the additive liquid is mixed with the resin or a resin raw material to prepare a mixture (molding composition). The latter method is particularly preferred because the operation is particularly simple.

[0129] In the mixture preparation step, a method of adding and dispersing near-infrared absorbing material particles in a resin will be described using an example of a method of using an additive liquid in which the above-mentioned near-infrared absorbing material particles are dispersed in an arbitrary dispersion medium.

[0130] In this case, prior to the mixture preparation step, an additive liquid is prepared by dispersing near-infrared absorbing material particles in a dispersion medium (additive liquid preparation step). Specifically, the additive liquid for producing a heat ray-shielding resin sheet material can be prepared by dispersing near-infrared absorbing material particles in an arbitrary dispersion medium using, for example, a bead mill, a ball mill, a sand mill, ultrasonic dispersion, or the like.

[0131] The dispersion medium used in the additive liquid for producing the heat-shielding resin sheet material is not particularly limited and can be selected according to the resin to be blended, the conditions for forming the resin sheet material, etc., and general organic solvents can be used. Furthermore, the pH of the additive liquid may be adjusted by adding an acid or alkali as needed. To further improve the dispersion stability of the near-infrared absorbing material particles in the resin, various surfactants, coupling agents, etc. can also be added to the additive liquid as dispersants.

[0132] Next, a mixture in which near-infrared absorbing material particles are dispersed in a resin can be prepared using the additive liquid (mixture preparation step). The mixture can be prepared, for example, by adding the additive liquid to a base resin and mixing or kneading. For example, the additive liquid and the resin components can be mixed using a ribbon blender or the like, and then melt-mixed as needed using a mixer such as a tumbler, Nauta mixer, Henschel mixer, super mixer, or planetary mixer, or a kneader such as a Banbury mixer, kneader, roll, single-screw extruder, or twin-screw extruder. In the obtained mixture, it is preferable that the near-infrared absorbing material particles are uniformly dispersed in the resin.

[0133] The resin used as the base material is not particularly limited, and as mentioned above, various transparent resins can be used, but polycarbonate resin or acrylic resin is preferably used from the viewpoints of optical properties, mechanical properties, raw material costs, etc.

[0134] The method for preparing a mixture in which near-infrared absorbing material particles are dispersed in a resin is not limited to the methods described above. For example, an additive liquid may be added to a resin raw material, the resin raw material is mixed, and then the resin raw material is reacted to form a resin, thereby preparing a mixture in which near-infrared absorbing material particles are dispersed in a resin. In this case, the mixture preparation step may include a mixture precursor preparation step in which the resin raw material and the additive liquid are mixed to prepare a mixture precursor, and a reaction step in which the resin raw material is reacted to prepare a mixture.

[0135] When the base resin is a polycarbonate resin, an additive liquid is added to a dihydric phenol, which is a raw material for the resin, and the mixture is uniformly mixed by a known method to prepare a mixture precursor. Next, a carbonate precursor, such as phosgene, is added to the mixture precursor and reacted to prepare a mixture in which near-infrared absorbing material particles are uniformly dispersed in the resin.

[0136] Furthermore, when the base resin is an acrylic resin, an additive liquid is added to methyl methacrylate, ethyl methacrylate, propyl methacrylate, butyl methacrylate, or the like, which are raw materials for the acrylic resin, and these are similarly uniformly mixed by a known method to prepare a mixture precursor. Next, the raw materials for the acrylic resin in the mixture precursor are polymerized by a known method such as suspension polymerization or bulk polymerization, thereby preparing a mixture in which near-infrared absorbing material particles are uniformly dispersed in the acrylic resin.

[0137] Alternatively, a mixture in which near-infrared absorbing material particles are dispersed in a resin can be prepared by removing the dispersion medium from the additive liquid by a known method, adding the obtained powder to a resin, and uniformly melt-mixing the powder.

[0138] The method for producing a heat ray-shielding resin sheet material of this embodiment can include, for example, a molding step of molding a mixture obtained by dispersing near-infrared shielding material particles in a resin as described above into a desired shape such as a flat shape or a curved shape by a known molding method such as injection molding, extrusion molding, compression molding, etc. Alternatively, a pelletizing step of once pelletizing a mixture obtained by dispersing near-infrared absorbing material particles in a resin using a granulator can be performed, and then a molding step of molding the mixture in the same manner except for using the pellets can be performed.

[0139] The molded body obtained in the molding step can also be used as the heat ray-shielding resin sheet material of this embodiment. Furthermore, as described below, if necessary, the molded body obtained in the molding step or other members can be bonded to form a heat ray-shielding resin sheet material.

[0140] The thickness of the molded product produced in the molding step is not particularly limited, and can be adjusted to any thickness as needed, for example, from a thick plate to a thin film.

[0141] The heat ray-shielding resin sheet material of the present embodiment is not limited to a layer containing near-infrared absorbing material particles, and may also have layers of other configurations, etc. Therefore, the manufacturing method of the heat ray-shielding resin sheet material of the present embodiment may include a step of forming a layer of other configurations, and may also include, for example, an ultraviolet absorbing film forming step or a hard coat layer forming step, which will be described below.

[0142] For example, the heat-shielding resin sheet material may have a resin coating containing an ultraviolet absorber on the surface of at least one sheet that is a molded body. That is, the heat-shielding resin sheet material of this embodiment may have an ultraviolet-absorbing film that is a resin coating containing an ultraviolet absorber, in addition to a near-infrared absorbing layer containing near-infrared absorbing material particles and a resin. For example, the manufacturing method of the heat-shielding resin sheet material of this embodiment may include an ultraviolet-absorbing film-forming step of applying a coating liquid in which an ultraviolet absorber such as a benzotriazole-based or benzophenone-based agent is dissolved in various binders onto the surface of one sheet that is a molded body obtained in the molding step, and curing the coating liquid to form an ultraviolet-absorbing film.

[0143] By having an ultraviolet absorbing film in the heat ray shielding resin sheet material, it is possible to further improve the weather resistance of the heat ray shielding resin sheet material, and also to provide the heat ray shielding resin sheet material with an ultraviolet shielding effect.

[0144] The heat-shielding resin sheet material may also have a hard coat layer having scratch resistance on at least one sheet surface. That is, the heat-shielding resin sheet material of this embodiment may have a hard coat layer in addition to the near-infrared absorbing layer containing near-infrared absorbing material particles and a resin. For example, the manufacturing method of the heat-shielding resin sheet material of this embodiment may include a hard coat layer formation step in which a scratch-resistant hard coat layer made of silicate, acrylic, or the like is formed on the surface of one sheet, which is the molded body obtained in the molding step. By forming the scratch-resistant hard coat layer, it is possible to improve the scratch resistance of the heat-shielding resin sheet material, and the heat-shielding resin sheet material may be suitably applied to vehicle and automobile windows, etc.

[0145] In this way, by dispersing near-infrared absorbing material particles having strong absorption in the near-infrared region as a heat ray shielding component in the resin and forming it into a sheet, it is possible to provide a heat ray shielding resin sheet material. According to the manufacturing method of the heat ray shielding resin sheet material of this embodiment, it is possible to provide a heat ray shielding resin sheet material having a heat ray shielding function and high transmittance in the visible light region without using a high-cost physical film formation method or a complicated bonding process.

[0146] The heat ray shielding resin sheet material of this embodiment can also be configured from a plurality of layers.

[0147] Specifically, as described above, the heat ray shielding resin sheet material may have, as sheet layers, a first surface sheet layer, a second surface sheet layer, an intermediate sheet layer, and a connecting sheet layer. Specific configuration examples have already been described, so description thereof will be omitted here.

[0148] Such a heat ray-shielding resin sheet material having multiple layers can be manufactured using, for example, a multilayer hollow sheet manufacturing device. Therefore, the sheet layers can be formed in the above-mentioned molding process. In this case, the heat ray-shielding resin sheet material of this embodiment can further include a lamination process in which multiple sheet layers are stacked and connected by a connecting sheet layer.

[0149] The heat-ray-shielding resin sheet material obtained by the manufacturing method for the heat-ray-shielding resin sheet material described above uses near-infrared absorbing material particles with excellent weather resistance, so the heat-ray-shielding resin sheet material also has excellent weather resistance and can stably shield heat rays over a long period of time. [Example]

[0150] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. (Evaluation method) First, the evaluation methods used in the following examples and comparative examples will be described. (1)Visible light transmittance, solar transmittance In each of the following examples, the visible light transmittance and solar radiation transmittance of the heat ray-shielding resin sheet material were measured using a spectrophotometer U-4000 manufactured by Hitachi, Ltd., and calculated in accordance with JIS R 3106 (2019). The solar radiation transmittance is an index showing heat ray-shielding performance.

[0151] The solar transmittance of the heat ray-shielding resin sheet material was also measured after the heat resistance test and the moist heat resistance test. The change in solar transmittance before and after the heat resistance test is shown as heat resistance ΔST in Table 1. The change in solar transmittance before and after the moist heat resistance test is shown as moist heat resistance ΔST in Table 1. The percentage change in solar transmittance before and after each test, ΔST, was calculated by subtracting the solar transmittance before exposure from the solar transmittance after exposure. (2) Haze value The haze value was measured using HR-200 manufactured by Murakami Color Research Laboratory Co., Ltd. in accordance with JIS K 7105 (1981). [Example 1] 23.5 g of Cs2CO3 was dissolved in 36 g of water, and this was added to 109 g of H2WO4 and thoroughly stirred, and then dried to obtain a raw material mixture according to Example 1 (raw material preparation step).

[0152] Next, the raw material mixture prepared in the raw material preparation step was used to carry out a reaction step using a hybrid plasma reactor 10 shown in FIG. 1 in which DC plasma (DC arc plasma) and high frequency plasma were superimposed.

[0153] First, the reaction system was evacuated to about 0.1 Pa (about 0.001 torr) using the vacuum exhaust device 13, and then completely replaced with argon gas to create an argon flow system at 1 atmosphere.

[0154] DC plasma was generated by flowing argon gas at 8 L / min through the plasma generating gas supply port 15. The DC power input at this time was 6 kW.

[0155] Furthermore, argon gas at 40 L / min and hydrogen gas at 3 L / min were spirally flowed from the sheath gas inlet 16 along the inner wall of the water-cooled quartz double tube 11 as gases for generating high-frequency plasma and protecting the quartz tube, to generate high-frequency plasma.

[0156] The input of the high frequency power supply was set to 45 kW. After generating such a hybrid plasma, the raw material mixture according to Example 1 was supplied into the plasma from the raw material powder supply device 19 at a supply rate of 2 g / min using a mixed gas of argon gas at 3 L / min and oxygen gas at 0.01 L / min as a carrier gas.

[0157] As a result, the raw material was instantly evaporated and condensed in the plasma tail flame to form fine particles. Particles (cesium tungsten oxide particles a), which are particles of the near-infrared absorbing material, were collected at the bottom of the reaction vessel 12.

[0158] The particle diameter of the collected cesium tungsten oxide particles a was determined by TEM observation, and it was confirmed that the particle diameter of the 30 particles evaluated was 10 nm or more and 50 nm or less. The particle diameter was calculated using the diameter of the smallest circle circumscribing the particle to be evaluated.

[0159] The results of quantitative analysis of Cs, W, and O of the recovered cesium tungsten oxide particles a were 14.7 wt%, 65.5 wt%, and 18.3 wt%, respectively. The chemical formula calculated from the quantitative analysis was Cs 0.31 WO 3.21 We were able to confirm that this is the case.

[0160] Cs was measured using a flame atomic absorption spectrometer (Varian, model: SpectrAA 220FS). W was measured using an ICP optical emission spectrometer (Shimadzu, model: ICPE9000). O was measured using an oxygen / nitrogen simultaneous analyzer (Leco, model: ON836). The same applies to the other examples and comparative examples below.

[0161] The X-ray diffraction pattern of the cesium tungsten oxide particles a was measured by powder X-ray diffraction (θ-2θ method) using a powder X-ray diffractometer (X'Pert-PRO / MPD manufactured by PANalytical, Spectris Co., Ltd.). The crystal structure of the compound contained in the cesium tungsten oxide particles a was identified from the obtained X-ray diffraction pattern, and it was found to be a hexagonal Cs 0.3 The same peaks as those of WO3 were confirmed. As described above, the crystal structure of the obtained composite tungsten oxide can be identified by the X-ray diffraction pattern. In the case of this example, as described above, the crystal structure of the compound contained in the composite tungsten oxide particles matches the peaks of a similar hexagonal composite tungsten oxide. Therefore, it can be confirmed that the crystal structure of the composite tungsten oxide obtained in this example, i.e., cesium tungsten oxide, is hexagonal.

[0162] Next, 5% by mass of the cesium tungsten oxide particles a, 5% by mass of an acrylic polymer dispersant having an amine-containing functional group (an acrylic dispersant with an amine value of 48 mg KOH / g and a decomposition temperature of 250°C), and 90% by mass of methyl isobutyl ketone were weighed out. The weighed raw materials were then ground and dispersed for 6 hours in a paint shaker (manufactured by Asada Iron Works) containing 0.3 mm diameter ZrO2 beads to prepare an additive solution (Solution A). The dispersed particle size of the cesium tungsten oxide particles a, which are near-infrared absorbing material particles, in the additive solution (Solution A) was measured using a particle size analyzer (ELS-8000, manufactured by Otsuka Electronics Co., Ltd.) based on dynamic light scattering, and was found to be 55 nm. After removing the solvent from Solution A, the cesium tungsten oxide particles, which are near-infrared absorbing material particles obtained from Solution A, were subjected to powder X-ray diffraction measurement (θ-2θ method) using a powder X-ray diffractometer (X'Pert-PRO / MPD manufactured by PANalytical, Spectris Co., Ltd.), and the crystallite size was calculated using the Rietveld method. The results are shown in Table 1.

[0163] Next, the obtained additive solution (Solution A) was added to polycarbonate resin so that the concentration of cesium tungsten oxide particles a was 0.0274 mass%, and the mixture was mixed in a blender, uniformly melt-kneaded in a twin-screw extruder, and then extrusion-molded to a thickness of 2 mm using a T-die. By extrusion molding, a heat-shielding polycarbonate sheet material (Sample 1), which is a heat-shielding resin sheet material in which near-infrared absorbing material particles are uniformly dispersed throughout the resin, was produced.

[0164] 1m of the obtained heat-shielding resin sheet material 2 The content of cesium tungsten oxide particles per unit area was 0.66 g. However, the specific gravity of the heat-shielding resin sheet material was 1.2 g / cm. 3The calculation was made as follows. Furthermore, it was confirmed by TEM observation (transmission electron microscope) that the particle diameter of the cesium tungsten oxide particles in the heat ray shielding resin sheet material was within the range of 10 nm to 50 nm. The particle diameter of the cesium tungsten oxide particles, which are near-infrared absorbing material particles, is shown in Table 1 in the column "Particle diameter of composite tungsten oxide in heat ray shielding resin sheet material." In Table 1, 10 nm to 50 nm is expressed as 10-50.

[0165] As shown in Table 1, when the visible light transmittance was 70.9%, the solar transmittance was 50.8%, and the haze value was 1.0%. The heat ray-shielding resin sheet was subjected to a moist heat resistance test by exposing it to an atmosphere of 85°C and 90% RH in the air for 94 hours. The solar transmittance of the heat ray-shielding resin sheet after the moist heat resistance test was also measured. As a result, the solar transmittance was 50.8%, and the moist heat resistance ΔST, which is the rate of change in solar transmittance before and after the moist heat resistance test, was 0.0%, confirming that the obtained heat ray-shielding resin sheet material had excellent moist heat resistance.

[0166] The obtained heat-shielding resin sheet material was also subjected to a heat resistance test by exposing it to 120°C in an atmospheric air for 125 hours. The solar radiation transmittance of the heat-shielding resin sheet used in the moist heat resistance test was also measured. As a result, the solar radiation transmittance was 50.5%, and the heat resistance ΔST, which is the rate of change in solar radiation transmittance, was -0.3%, indicating excellent heat resistance.

[0167] [Example 2] A vacuum dryer was used to remove the organic solvent from the additive liquid (liquid A) prepared in Example 1, thereby preparing a powder (powder A) for a heat ray-shielding resin sheet material. Next, the obtained powder (powder A) was added to polycarbonate resin so that the concentration of cesium tungsten oxide particles a was 0.0274 mass%, mixed in a blender, uniformly melt-kneaded in a twin-screw extruder, and then extrusion-molded to a thickness of 2 mm using a T-die. By extrusion molding, a heat ray shielding polycarbonate sheet material (sample 2) was produced, which is a heat ray shielding resin sheet material in which near infrared absorbing material particles are uniformly dispersed throughout the resin.

[0168] Except for the above points, a heat ray-shielding resin sheet material was produced and evaluated in the same manner as in Example 1. The evaluation results are shown in Table 1.

[0169] [Example 3] The additive liquid (liquid A) prepared in Example 1 was added to polycarbonate resin so that the concentration of cesium tungsten oxide particles a was 0.0265 mass%, and the resin was molded using a hollow three-layer sheet manufacturing die so that each sheet layer had a thickness of 0.7 mm and the total thickness was 20 mm. The obtained heat ray-shielding resin sheet material had the same cross-sectional shape as the heat ray-shielding resin sheet material with a hollow three-layer structure shown in Figure 3, and all of the sheet layers contained cesium tungsten oxide particles a, which are near-infrared absorbing material particles.

[0170] Except for the above points, a heat ray shielding resin sheet material (sample 3) was produced and evaluated in the same manner as in Example 1. The evaluation results are shown in Table 1.

[0171] [Example 4] The additive solution (solution A) prepared in Example 1 was added to polycarbonate resin so that the concentration of cesium tungsten oxide particles a was 1.1% by mass, mixed in a blender, uniformly melt-kneaded in a twin-screw extruder, and then co-extrusion molded to a thickness of 50 μm onto a 2 mm thick polycarbonate sheet. By co-extrusion molding, a heat-shielding polycarbonate laminate (sample 4) was produced, which is a heat-shielding resin sheet material laminate in which near-infrared absorbing material particles are uniformly dispersed in the upper layer with a thickness of 50 μm. Except for the above points, the same operation as in Example 1 was performed to produce a heat-shielding resin sheet material laminate and evaluate it. The evaluation results are shown in Table 1.

[0172] [Example 5] Near-infrared absorbing material particles were prepared using a high-frequency plasma reactor 30 shown in FIG.

[0173] The high frequency plasma reactor 30 has a water-cooled quartz double tube 31 and a reaction vessel 32 connected to the water-cooled quartz double tube 31. A vacuum exhaust device 33 is connected to the reaction vessel 32.

[0174] Above the water-cooled quartz double tube 31, a plasma generating gas supply port 34 is provided.

[0175] The water-cooled quartz double tube 31 is configured so that sheath gas for generating high-frequency plasma and for protecting the quartz tube can be supplied along the inner wall thereof, and a sheath gas inlet 36 is provided on the upper flange of the water-cooled quartz double tube 31.

[0176] A water-cooled copper coil 37 for generating high-frequency plasma is arranged around the water-cooled quartz double tube 31 .

[0177] A raw material powder carrier gas supply port 38 is provided near the plasma generating gas supply port 34 and is connected by a pipe to a raw material powder supply device 39 that supplies raw material powder.

[0178] The plasma generating gas supply port 34, sheath gas inlet 36, and raw material powder supply device 39 can be connected to a gas supply device 40 by piping, so that a predetermined gas can be supplied to each component from the gas supply device 40. Note that, if necessary, supply ports other than those for the components mentioned above can be provided and connected to the gas supply device 40 so that the components in the device can be cooled or a predetermined atmosphere can be created.

[0179] In this example, high-frequency plasma was generated by first flowing argon gas at 30 L / min through the plasma generating gas supply port 34, and then supplying a mixture of argon gas at 40 L / min and hydrogen gas at 3 L / min in a spiral fashion through the sheath gas inlet 36. The high-frequency power input at this time was 45 kW.

[0180] Next, the raw material mixture prepared in Example 1 was supplied into the plasma at a rate of 2 g / min from raw material powder supply device 39 using a mixed gas of argon gas at 3 L / min and oxygen gas at 0.01 L / min as a carrier gas.

[0181] As a result, the particle diameter of the near-infrared absorbing material particles recovered at the bottom of the reaction vessel 32 was found to be 10 nm or more and 50 nm or less by TEM observation.

[0182] The X-ray diffraction pattern of the obtained near-infrared absorbing material particles according to Example 5 was measured by powder X-ray diffraction (θ-2θ method). The crystal structure contained in the particles was identified from the obtained X-ray diffraction pattern, and it was found to be hexagonal Cs 0.3 The same peak as that of WO3 was confirmed.

[0183] Except for using the obtained composite tungsten oxide particles, which are near-infrared absorbing material particles according to Example 5, an additive solution was prepared in the same manner as in Example 1, and then a heat ray-shielding polycarbonate sheet material according to Example 5 was produced. The evaluation results are shown in Table 1.

[0184] The dispersed particle diameter of the composite tungsten oxide particles, which are near-infrared absorbing material particles in the additive liquid according to Example 5, was 55 nm. [Example 6] A heat ray-shielding resin sheet material was produced and evaluated in the same manner as in Example 5, except that a mixed gas of 5 L / min of argon gas and 0.01 L / min of oxygen gas was used as the carrier gas. The evaluation results are shown in Table 1.

[0185] The dispersed particle diameter of the composite tungsten oxide particles, which are near-infrared absorbing material particles in the additive liquid according to Example 6, was 54 nm. [Example 7] A heat ray-shielding resin sheet material was produced and evaluated in the same manner as in Example 1, except that a mixed gas of argon gas at 4 L / min and oxygen gas at 0.01 L / min was used as the carrier gas. The evaluation results are shown in Table 1.

[0186] The dispersed particle diameter of the composite tungsten oxide particles, which are near-infrared absorbing material particles in the additive liquid according to Example 7, was 55 nm. [Example 8] A heat ray-shielding resin sheet material was produced and evaluated in the same manner as in Example 1, except that, when preparing the raw material mixture, Na2CO3 and H2WO4 were weighed out in predetermined amounts so that the molar ratio of W to Na was 1:0.50. The evaluation results are shown in Table 1.

[0187] The dispersed particle diameter of the composite tungsten oxide particles, which are near-infrared absorbing material particles in the additive liquid according to Example 8, was 56 nm. [Example 9] A heat ray-shielding resin sheet material was produced and evaluated in the same manner as in Example 1, except that, when preparing the raw material mixture, K2CO3 and H2WO4 were weighed out in predetermined amounts so that the molar ratio of W to K was 1:0.33. The evaluation results are shown in Table 1.

[0188] The dispersed particle diameter of the composite tungsten oxide particles, which are near-infrared absorbing material particles in the additive liquid according to Example 9, was 58 nm. [Example 10] A heat ray-shielding resin sheet material was produced and evaluated in the same manner as in Example 1, except that when preparing the raw material mixture, Rb2CO3 and H2WO4 were weighed out in predetermined amounts so that the molar ratio of W to Rb was 1:0.30. The evaluation results are shown in Table 1.

[0189] The dispersed particle diameter of the composite tungsten oxide particles, which are near-infrared absorbing material particles in the additive liquid according to Example 10, was 57 nm. [Example 11] A heat ray-shielding resin sheet material was produced and evaluated in the same manner as in Example 1, except that, when preparing the raw material mixture, BaCO3 and H2WO4 were weighed and used in predetermined amounts so that the molar ratio of W to Ba was 1:0.30. The evaluation results are shown in Table 1.

[0190] The dispersed particle diameter of the composite tungsten oxide particles, which are near-infrared absorbing material particles in the additive liquid according to Example 11, was 60 nm. [Example 12] A heat ray-shielding resin sheet material was produced and evaluated in the same manner as in Example 1, except that, when preparing the raw material mixture, In2O3 and H2WO4 were weighed out in predetermined amounts so that the molar ratio of W to In was 1:0.30. The evaluation results are shown in Table 1.

[0191] The dispersed particle diameter of the composite tungsten oxide particles, which are near-infrared absorbing material particles in the additive liquid according to Example 12, was 59 nm. [Example 13] A heat ray-shielding resin sheet material was produced and evaluated in the same manner as in Example 1, except that when preparing the raw material mixture, TlNO3 and H2WO4 were weighed out in predetermined amounts so that the molar ratio of W to Tl was 1:0.30. The evaluation results are shown in Table 1.

[0192] The dispersed particle diameter of the composite tungsten oxide particles, which are near-infrared absorbing material particles in the additive liquid according to Example 13, was 62 nm. [Example 14] In preparing the raw material mixture, K2CO3 and H2WO4 were weighed out in predetermined amounts so that the molar ratio of W to K was 1:0.55, and other than this, the same operations as in Example 1 were carried out to produce and evaluate heat ray-shielding resin sheet materials. The evaluation results are shown in Table 1.

[0193] The dispersed particle diameter of the composite tungsten oxide particles, which are near-infrared absorbing material particles in the additive liquid according to Example 14, was 57 nm. [Example 15] A heat ray shielding resin sheet material was produced and evaluated in the same manner as in Example 1, except that an acrylic resin was used instead of the polycarbonate resin. The evaluation results are shown in Table 1. [Comparative Example 1] 286g of tungstic acid (H2WO4) was added to an aqueous solution of 55.45g of cesium carbonate (Cs2CO3) dissolved in 50g of water, and the mixture was thoroughly stirred and then dried. The molar ratio of W to Cs in the dried product was W:Cs = 1:0.33.

[0194] The dried product was fired at 800°C for 5.5 hours in a 5% H gas atmosphere with N gas as a carrier gas. Thereafter, the supply gas was switched to only N gas, and the temperature was lowered to room temperature to obtain cesium tungsten oxide particles, which are near-infrared absorbing material particles according to Comparative Example 1.

[0195] The X-ray diffraction pattern of the obtained near-infrared absorbing material particles according to Comparative Example 1 was measured by powder X-ray diffraction (θ-2θ method). The crystal structure contained in the particles was identified from the obtained X-ray diffraction pattern, and it was found to be hexagonal Cs 0.3 The same peak as that of WO3 was confirmed.

[0196] 5% by mass of the near-infrared absorbing material particles according to Comparative Example 1, 5% by mass of the same acrylic polymer dispersant as in Example 1, and 90% by mass of methyl isobutyl ketone were weighed out, loaded into a paint shaker (manufactured by Asada Iron Works) containing 0.3 mm diameter ZrO2 beads, and subjected to a pulverization and dispersion treatment for 30 hours. In this way, an additive liquid according to Comparative Example 1 was prepared. The dispersed particle diameter of the composite tungsten oxide particles, which are near-infrared absorbing material particles, in the additive liquid was 64 nm.

[0197] Except for using the additive liquid, a heat ray-shielding polycarbonate sheet material, which is a heat ray-shielding resin sheet material according to Comparative Example 1, was produced in the same manner as in Example 1. The evaluation results are shown in Table 1.

[0198] [Table 1] [evaluation] When examining the solar transmittance of the heat-shielding resin sheet materials of Examples 1 to 15 and Comparative Example 1 based on the various properties listed in Table 1, the solar transmittance at visible light transmittances of 75.0% or less was all less than 67.0%.

[0199] It was confirmed that the heat ray-shielding resin sheet materials of Examples 1 to 15 had excellent weather resistance, with moist heat resistance ΔST and heat resistance ΔST both being less than 1.0%. In contrast, it was confirmed that the moist heat resistance ΔST and heat resistance ΔST of the heat ray-shielding resin sheet material of Comparative Example 1 exceeded 1.0%.

[0200] That is, it was confirmed that the heat ray shielding resin sheet materials of Examples 1 to 15 contain near infrared absorbing material particles that are excellent in weather resistance, and that the resin sheet materials also have excellent weather resistance. [Explanation of symbols]

[0201] 50, 60 Heat ray shielding resin sheet material 501, 601 1st outer surface 502, 602 2nd outer surface 51, 61 First surface sheet layer 52, 62 Second surface sheet layer 53 Intermediate sheet layer 63 First intermediate sheet layer 64 Second intermediate sheet layer 65 Third intermediate sheet layer 66 4th intermediate sheet layer 54 Connecting Sheet Layer 67 First connection sheet layer 68 Second connection sheet layer

Claims

1. Contains near infrared absorbing material particles and a resin, The near infrared absorbing material particles are represented by the general formula M x W y O z (wherein M element is one or more elements selected from Na, K, Rb, Cs, Ba, In, and Tl, W is tungsten, O is oxygen, 0.20≦x / y≦0.37, 3.0<z / y<3.4)

2. 2. The heat ray shielding resin sheet material according to claim 1, wherein the composite tungsten oxide particles contain crystals having one or more crystal structures selected from hexagonal, tetragonal, and cubic crystals.

3. 3. The heat ray shielding resin sheet material according to claim 1, wherein the particle diameter of the near infrared ray absorbing material particles is 10 nm or more and 100 nm or less.

4. The heat ray shielding resin sheet material according to claim 1 , wherein the resin is a polycarbonate resin or an acrylic resin.

5. The sheet has a plurality of sheet layers containing at least the resin, Among the plurality of sheet layers, at least one of the sheet layers contains the near infrared absorbing material particles, The sheet layers include a first surface sheet layer, a second surface sheet layer, an intermediate sheet layer, and a connection sheet layer, the first surface sheet layer, the intermediate sheet layer, and the second surface sheet layer are laminated in that order, and the connecting sheet layer connects the first surface sheet layer, the intermediate sheet layer, and the second surface sheet layer; the first surface sheet layer includes a first surface which is an outer surface of the heat ray shielding resin sheet material, the second surface sheet layer includes a second surface that is an outer surface of the heat ray shielding resin sheet material and is located on the opposite side to the first surface, 5. The heat ray shielding resin sheet material according to claim 1, further comprising a hollow multi-layer structure including a gap between the first surface sheet layer and the second surface sheet layer.

6. 6. The heat ray shielding resin sheet material according to claim 5, wherein all of the sheet layers contain the near infrared ray absorbing particles.

7. 6. The heat ray shielding resin sheet material according to claim 5, wherein only one of the first surface sheet layer and the second surface sheet layer contains the near infrared ray absorbing particles.

8. 6. The heat ray shielding resin sheet material according to claim 5, wherein only the first surface sheet layer and the second surface sheet layer contain the near infrared ray absorbing particles.

Citation Information

Patent Citations

  • Tungsten-containing metal oxide nano particle and preparation method thereof

    CN106978005A

  • Tungsten-containing metal oxide nanoparticle dispersoid and preparation method thereof

    CN107083101A

  • Solar thermal insulating coating, solar thermal insulating film and solar thermal insulating glass

    CN107083179A

  • Heat ray screening plate

    JP1990173060A

  • Heat-reflecting plate

    JP1993078544A